2007
DOI: 10.1359/jbmr.070721
|View full text |Cite
|
Sign up to set email alerts
|

Patients With High Bone Mass Phenotype Exhibit Enhanced Osteoblast Differentiation and Inhibition of Adipogenesis of Human Mesenchymal Stem Cells

Abstract: Genetic mutations in the LRP5 gene affect Wnt signaling and lead to changes in bone mass in humans. Our in vivo and in vitro results show that activated mutation T253I of LRP5 enhances osteogenesis and inhibits adipogenesis. Inactivating mutation T244M of LRP5 exerts opposite effects.Introduction: Mutations in the Wnt co-receptor, LRP5, leading to decreased or increased canonical Wnt signaling, result in osteoporosis or a high bone mass (HBM) phenotype, respectively. However, the mechanisms whereby mutated LRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
128
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(136 citation statements)
references
References 55 publications
4
128
1
3
Order By: Relevance
“…For example, biased MSC differentiation toward adipogenesis is strongly related to osteoporosis and other chronic bone loss diseases (3). Similarly, an increased number of adipocytes and a decreased number of osteoblasts are often found in age-related physiological bone reduction (4).…”
Section: Multipotent Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
“…For example, biased MSC differentiation toward adipogenesis is strongly related to osteoporosis and other chronic bone loss diseases (3). Similarly, an increased number of adipocytes and a decreased number of osteoblasts are often found in age-related physiological bone reduction (4).…”
Section: Multipotent Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
“…This pathway is a key regulator of the differentiation of mesenchymal stem cells toward chondrocytes, osteoblasts, or adipocytes. The Wnt/b-catenin signaling pathway has been shown to inhibit the adipogenic differentiation potential, thus altering the fate of cells from adipocytes to osteoblasts (137,138,139,140). This is induced by suppressing the expression of the adipogenic transcription factors peroxisome proliferator-activated receptor g (PPARg (PPARG)) and CCAAT/enhancer-binding protein a (C/EBPa (CEBPA)) (141).…”
Section: Evidence For a Role Of Canonical Wnt Signaling In Bone Formamentioning
confidence: 99%
“…With the identification of the highly interesting bone phenotype of increased bone mass and strength in the HBM patients, who have loss-of-inhibition mutations in LRP5 (15,109,140,160,168), an intensive search for therapies targeting this molecule was initiated. As the Wnt ligands, as well as the downstream signaling molecules GSK3b and b-catenin, are rather ubiquitous and have been implicated in cancer progression, these are less attractive targets despite their obvious anabolic potential (169,170).…”
Section: The Wnt/lrp5 Systemmentioning
confidence: 99%
“…(10) However, other studies have reported that canonical Wnt signaling inhibits MSC proliferation. (11) The use of a Dkk1 blocker induced MSCs to reenter the cell cycle through antagonizing canonical Wnt signaling. (12) Moreover, Wnt/b-catenin signaling was reported to shift MSC cell fate toward osteoblastogenesis at the expense of adipogenesis (13) and increases bone mass in osteopenic rats.…”
Section: Introductionmentioning
confidence: 99%